The Effect of Diabetes on Induced Pain of Formalin and Baclofen Analgesia in Rats - Nooshinfar, Elaheh; Hamidpoor, Mohsen; Akbarzadeh - Baghban, Ali Reza; Mansoori, Vahid; Salahi Yekta, Ali; Hossein Heidari, Mohammad; Koosha, Soheila (Archives of Advances in Biosciences, 2010)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-language:FA;} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; mso-ascii-font-family:Calibri; mso-fareast-font-family:Calibri; mso-hansi-font-family:Calibri; mso-bidi-font-family:Arial;} @page Section1 {size:8.5in 11.0in; margin:1.0in 1.0in 1.0in 1.0in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> One of the side effects of dibetecs epidemics today in the world is painfulneuropathy, the reasons and treatments of which are unknown. Duo to the importance of problem of pain treatment as on of the harmful phenomena in life, this research studies the effect of continued diabetes on the formalin induced pain and baclofen analgesia in rats. Moreover the effect of baclofen as a non-opiate, analgesic drug on the increased pains in the quiescent phase as the model of diabetic pain is investigated. The method is experimental, evaluating the pain level through conducting the formalin test in 3 groups of rats. The first group was divided to control (injection normal salin) and diabetc (injection aloxan 100mg per kg) which were tested, after one to four weeks from the begining of diabetes, the second one was divided to a new control and diabetic group, and before performing formalin test, the baclofen(10mg per kg) was injected to them. And the third one was divided to two diabetics groups that received baclofen and normal salin and then the pain of the quiescent phase was compared in them. The results indicate that diabetes increases formalin induced pain and remained with continud diabetes. It also indicate that diabetes establishes increased pain in the quiscent phase , yet, it has had no influene on the baclofen analgesic effect on the first phase of formalin test but increased it on the second phase. Moreover baclofen can quiet the increased pain in quiscent phase very well. Duo to the results of this study it seems that diabetes, with changes in the centeral and peripheral pathways of the pain and also pain control, increases the pain. More studies are required to determining its mechanisms. These changes are accompanied with weakening the internal antipain systems such as Gaba ergic, which can be treated with baclofen . Diabetes has no intraction with the baclofen analgesics effect, so, baclofen may be recommended as an effective drug to comfort painful diabetic neurophathy. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-language:FA;} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; mso-ascii-font-family:Calibri; mso-fareast-font-family:Calibri; mso-hansi-font-family:Calibri; mso-bidi-font-family:Arial;} @page Section1 {size:8.5in 11.0in; margin:1.0in 1.0in 1.0in 1.0in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]-->